„Hakowanie systemu”. O mobilizowaniu zasobów i strategiach działań akademików wywodzących się z klas ludowych - Tobiasiewicz, Edyta; Łuczaj, Kamil (Człowiek i Społeczeństwo, 2023)
The paper presents the results of the analysis of 25 biographical narrative interviews conducted between 2020–2021 with people from working-class backgrounds who, in the process of becoming academic workers, experienced the costs of cultural mobility. International literature suggests that upward mobility is not only a source of satisfaction or prestige but also suffering for academics from the unprivileged classes. Therefore, in our paper, we aim to answer two research questions: (1) what adaptation strategies do academics from the working-class use to deal with difficult experiences?, and (2) what resources do they mobilize at different stages of life (childhood, school years, the beginning of a research career) to implement these strategies? The analysis of empirical material allowed us to distinguish a number of practices that, in the long term, enabled the interviewees to develop an academic career, e.g., collaboration with “significant others” (of higher social positions), hiding deficits of a capital, context-dependent manifestation of various sets of cultural practices, or the rebellion against the rules and norms present in the family or academic environment. Based on these practices, we define six categories of adaptation strategies: “hacking the system”, “hyper-productivity”, “borrowing capital”, “class manoeuvring”, “indirect career path”, and “resistance”.